Concept of Islamic Law Enforcement In the History and Practice of Islamic Justice - Syam, Misnar; Devianty Fitri (Dinasti Research, 2024)
Upholding justice in social life has an important meaning in one of the efforts to build a high and dignified national civilization. Justice is carried out by judicial institutions. The performance of our courts or justice system is far from satisfactory, which results in a sense of comfort and happiness for justice seekers. Court decisions only create decisions that are procedurally fair. Likewise, court decisions seem more likely to favor parties who have money and power. Access to justice that should be equal for all levels of society cannot be achieved, so only elite people can enjoy it. In administering the judicial process, Islamic law aims to enforce law and justice proportionally based on Islamic Sharia. The growth and development of Islamic justice is a product of interactions within the social system, including with existing judicial institutions. Law enforcement in Indonesia does not synergize with each other in realizing justice. This is due to the position and standing of legal institutions where the function of investigation and prosecution is under executive power, while the function of adjudicating and deciding is under the Supreme Court. This causes a tendency to protect the interests of their respective institutions rather than law enforcement efforts in the public interest. The problem formulation in this paper is what is the concept of law enforcement in Islamic law in the practice and history of Islamic justice? The conclusion is:The concept of law enforcement in Islamic law does not differentiate between civil and criminal cases. Law enforcement includes material law and formal law. Material law originates from the Al-Qur'an, As-Sunnah and Fiqh.